2007
DOI: 10.1124/jpet.107.126219
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Levodopa Dose and Magnitude of Dopamine Depletion as Risk Factors for Levodopa-Induced Dyskinesia in a Rat Model of Parkinson's Disease

Abstract: Levodopa dose and severity of Parkinson's disease (PD) are recognized risk factors for levodopa-induced dyskinesia (LID) in humans. The purpose of the present study was to evaluate the ability of these variables to predict severity of LID in a rat model of PD. Varied concentrations of 6-hydroxydopamine were injected into the midbrain to produce wide ranges of dopamine depletion in striatum. Three weeks later, rats were given daily injections of levodopa (2-10 mg/kg i.p.) plus benserazide (12.5 mg/kg i.p.) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
48
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 41 publications
(56 reference statements)
9
48
1
Order By: Relevance
“…S5C), consistent with the literature using this model (2,(30)(31)(32)(33)(34). Acute treatment with L-DOPA-induced pERK in predominantly medium-sized neurons and repeated L-DOPA administration reduced the number of medium-sized pERK-labeled cells by 72% and increased the number of large-diameter pERK-labeled neurons by 3.4-fold in lesioned striatum (Fig.…”
Section: Cholinergic Neuronal Hyperactivity Correlates With Lid In Unsupporting
confidence: 80%
See 1 more Smart Citation
“…S5C), consistent with the literature using this model (2,(30)(31)(32)(33)(34). Acute treatment with L-DOPA-induced pERK in predominantly medium-sized neurons and repeated L-DOPA administration reduced the number of medium-sized pERK-labeled cells by 72% and increased the number of large-diameter pERK-labeled neurons by 3.4-fold in lesioned striatum (Fig.…”
Section: Cholinergic Neuronal Hyperactivity Correlates With Lid In Unsupporting
confidence: 80%
“…Unilateral 6-OHDA lesions used in this study produced massive striatal DA depletions of 94%, covering the entire striatum, whereas striatal DA depletion is limited to the most dorsal aspect of dorsal striatum in Pitx3 ak/ak mice. LID has been reported with the first exposure to L-DOPA in unilateral 6-OHDA-lesioned rats (2,(30)(31)(32)(33)(34) and the level of dyskinetic behavior is influenced by the amount of DA loss (34). Therefore, we believe the Pitx3 ak/ak mice show the time course more consistent with mild to moderate PD, whereas 6-OHDAlesioned mice model a more severe stage of PD.…”
Section: Discussionmentioning
confidence: 72%
“…The fact that dyskinesia can emerge very quickly in severely affected or young people with PD is consistent with this argument, 10,11 as is the observation that dyskinesia can be seen with the first dose of levodopa in rodents and monkeys with toxin-induced parkinsonism. 12,13 The second important observation of this study is that the antiparkinsonian responses and the dyskinesia response evolved in a similar manner during the first 4 years of levodopa therapy. With time, both the increase in tapping speed and dyskinesia began with a shorter latency during the 2-hour levodopa infusions.…”
Section: Dyskinesia and Antiparkinsonian Responsementioning
confidence: 88%
“…Significant modifications from Cenci et al [9] include the use of males, altered lesion coordinates, desipramine to protect noradrenergic neurons, and a higher 6-OHDA dose. Our collaborators recently demonstrated that severe dopamine depletion is necessary but not sufficient to evoke dyskinesias and reviewed factors that may affect dyskinesia emergence [10].…”
Section: Discussionmentioning
confidence: 99%